Exposure to psychosocial job strain during pregnancy and odds of asthma and atopic dermatitis among 7-year old children – a prospective cohort study - Larsen, Ann Dyreborg; Schlünssen, Vivi; Christensen, Berit Hvass; Bonde, Jens Peter; Obel, Carsten; Thulstrup, Ane Marie; Hannerz, Harald; Hougaard, Karin Sørig (Scandinavian Journal of Work, Environment & Health, 2014)
' ' OBJECTIVES ': 'Few epidemiological studies have studied maternal stress exposure during pregnancy and odds of asthma and atopic dermatitis (AD) among offspring, and none have extended the focus to psychosocial job strain. The aim of this study was to assess the association between maternal job strain during pregnancy and asthma as well as AD among 7-year-old children. ' ' METHODS ': 'The study is based on the Danish National Birth Cohort and includes prospective data from 32 104 pregnancies. Job strain was assessed early in pregnancy by use of two questions on demands and control. We categorized participants into four job strain categories: low strain (low demands, high control), active (high demands, high control), passive (low demands, low control), and high strain (high demands, low control). Information on asthma and AD until age seven was collected using maternal self-report. Multinomial logistic regression models were used to estimate odds ratios (OR) with 95% confidence intervals (95% CI) adjusted for several covariates. ' ' RESULTS ': 'Maternal exposure to self-reported high strain during pregnancy was associated with 15% higher odds of atopic dermatitis among 7-year-old children (ORadj 1.15, 95% CI 1.02–1.31). Furthermore, an association between the active jobs and asthma among 7-year-old children was found (ORadj 1.13, 95% CI 1.03–1.24). ' ' CONCLUSION ': 'Maternal exposure to high strain and active jobs during pregnancy was associated with asthma and atopic dermatitis among 7-year-old children.
Keywords: allergic disease; asthma; atopic dermatitis; birth cohort; children; Danish National Birth Cohort; exposure; high demand; job control; job demand; job strain; low control; offspring; pregnancy; prenatal stress; psychosocial; psychosocial job strain